Effect of a nutrition intervention on eating behaviours and body composition among elite adolescent ballet students - Hans Hauner; Dorothy Meyer; Marc Geifes (BMJ Nutrition, Prevention & Health)
Objective The primary goal of this study was to assess whether a nutrition education programme had an effect on nutrition literacy and body composition of adolescents enrolled in an undergraduate ballet programme.Methods 27 students, aged 15–18, volunteered and provided informed consent following ethics approval. The nutrition programme included two workshops and four cooking classes throughout the academic year, with an additional workshop for female students on low energy availability’s effects on menstrual function. Each participant also attended two individual counselling sessions with a nutritionist to develop personalised nutrition goals. Data were collected at baseline, postintervention (9 months later) and follow-up (12 months from baseline). Eating attitudes and behaviours were assessed using the Eating Disorder Examination Questionnaire–Adolescents (EDE-A), the Dance-specific Energy Availability Questionnaire and a survey developed by researchers. Body composition was measured using a body impedance analysis scale. Changes from baseline were analysed with Wilcoxon signed-rank tests.Results Students showed improvements in several aspects of eating self-efficacy and nutrition knowledge postintervention. Though no change in mean EDE-A scores were observed, fewer students reached clinically significant scores postintervention and at follow-up. Female participants showed significant increases in body mass index (BMI) (Z=−2.527, p=0.011) and lean body mass (Z=−3.102, p=0.002) postintervention, which persisted at follow-up.Conclusions This study suggests that a nutrition programme can lead to improvements in eating attitudes and behaviours among undergraduate ballet students, demonstrating its importance in dance education. In addition, positive changes in BMI and lean body mass of female students were observed. Ongoing research is needed to establish best practices in this population of adolescent dancers at increased risk of nutritional deficits.